1995
DOI: 10.1248/bpb.18.64
|View full text |Cite
|
Sign up to set email alerts
|

A Saturable Tissue-Angiotensin I Converting Enzyme (ACE) Binding Model for the Pharmacokinetic Analysis of Imidapril, a New ACE Inhibitor, and Its Active Metabolite in Human.

Abstract: In order to obtain a rational explanation and analytical method of the unique pharmacokinetic behaviors of imidapril and imidaprilat in human, a new pharmacokinetic model was designed by introducing a saturable-reversible angiotensin I converting enzyme (ACE)-imidaprilat binding process and a linear imidapril-imidaprilat conversion process. According to the new model, six differential equations were given which considered the mass balance of both compounds in each component. Various pharmacokinetic parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Therefore, intact VY absorption was estimated to be much slower than that of other peptides 20 . This slow absorption of VY is comparable with that of the clinical ACE inhibitor imidapril, for which maximal plasma concentrations have been observed 2 h after administration to healthy human volunteers 21 18 …”
Section: Discussionmentioning
confidence: 88%
“…Therefore, intact VY absorption was estimated to be much slower than that of other peptides 20 . This slow absorption of VY is comparable with that of the clinical ACE inhibitor imidapril, for which maximal plasma concentrations have been observed 2 h after administration to healthy human volunteers 21 18 …”
Section: Discussionmentioning
confidence: 88%
“…16) Oral administration study of prodrug-type ACE inhibitor, imidapril, to healthy human, 17) on the other hand, demonstrated that the plasma concentration reached a maximal level (C max at 10 mg-dose) of 70 pmol/ml-plasma after 2 h (T max ; 2 h). While the absorption profile of imidapril with T max of 2 h was in good agreement with that in our present VY-study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Imidapril ( 1 mg/kg) was administered by gastric tube daily. The selection of dose and route of administration of this agent are based on previous studies ( 19,20,23). Such treatment of infarcted rats with imidapril has been shown to prevent the activation of cardiac and circulating ACE.…”
Section: Administration Of Imidaprilmentioning
confidence: 99%
“…Imidapril, (4S)-l-methyl-3-((2S)-2-[N-((IS)-l-ethoxycarbonyl-3-phenylpropyl)-amino] propionyl)-2-oxo-imidazolidine-4-carboxylic acid, is a non-sulfhydryl-containing ACE inhibitor similar to enalapril (18)(19)(20). We studied the effects of imidapril in rats because the time course for arrhythmias and mortality during acute myocardial infarction are well characterized in this species (21).…”
mentioning
confidence: 99%